GDF11 restores the impaired function of EPCs-MA by promoting autophagy: GDF11 ameliorates endothelial progenitor cell aging by promoting autophagy - Liu Donghua; Zhang Yang; Liu Xin; Huang Qihe; Zhang Xiaofang; Yang Rui; Zhao Yue; Li Penghui; He Jiayi; Zhang Kexiao; Pan Zhenwei; Liu Huiwen; et al. (Frigid Zone Medicine)
Our study aimed to assess the effects of Growth and differentiation factor 11 (GDF11) on the function of endothelial progenitor cells in middle-age individuals (EPCs-MA) isolated from mouse bone marrow and to explore the mechanistic relationship between GDF11 and age-related ALP impairment.